Zhodnocení finanční situace podniku a návrhy na její zlepšení - Hortová, Monika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Diplomová práce hodnotí finanční situaci podniku TOR Cheb, spol. s r.o. v letech 2007 až 2011 a formuluje návrhy opatření na zlepšení v problémových oblastech. Teoretická část práce vymezuje základní termíny, metody a ukazatele. Praktická část práce podnik charakterizuje a dále hodnotí jeho výnosovou situaci a finanční stabilitu na základě vybraných metod finanční analýzy. Interpretace výsledků je východiskem pro návrhovou část diplomové práce.

The diploma thesis evaluates the financial situation of the company TOR Cheb, spol. s r.o. during the years 2007 to 2011, and formulates proposals for improvement of the problematic areas. The theoretical part defines basic terms, methods and indicators. The practical part of the thesis characterizes the firm, and evaluates its performance and financial stability on the basis of selected methods of financial analysis. The interpretation of these results is the starting point for the proposal part of the thesis.
Assessment of the Financial Situation in the Firm and Proposals to its Improvement
Keywords: Finanční analýza; horizontální analýza; vertikální analýza; poměrová analýza; rozdílové ukazatele.; Financial analysis; financial statements; horizontal analysis; vertical analysis; ratio analysis; differential indicators.